Incidence, predictors and clinical outcome of early bleeding events in patients undergoing a left ventricular assist device implant. (22nd February 2018) - Muslem, Rahatullah; Caliskan, Kadir; van Thiel, Robert; Kashif, Usman; Akin, Sakir; Birim, Ozcan; Constantinescu, Alina A; Brugts, Jasper J; Bunge, Jeroen J H; Bekkers, Jos A; Leebeek, Frank W G; Bogers, Ad J J C
Abstract: OBJECTIVES: Bleeding is a common complication following left ventricular assist device (LVAD) implantation. The goal of this study was to investigate the incidence, predictors and clinical outcome of early bleeding events in patients after LVAD implantation. METHODS: A total of 83 patients (age 50 ± 13 years, 76% men) had an LVAD implanted [77% HeartMate II, 19% HeartMate 3 (Abbott, Chicago, IL, USA)] over a period of 11 years. Patients were included consecutively. An early bleeding event was defined as the need for thoracic surgical re-exploration or transfusion with >4 units of packed red blood cells before discharge. RESULTS: Overall, 39 (47%) patients (age 50 ± 14 years, 77% men) experienced an early bleeding event [median time 6 days (interquartile range 1–9 days)]. Furthermore, 10 (26%) of these patients had ≥2 bleeding events. Twelve of the 14 (92%) patients with venoarterial extracorporeal membrane oxygenation (ECMO) support before LVAD implantation experienced an early bleeding event versus 27 of the 69 (39%) patients without ECMO support ( P  < 0.001). No difference was found in early bleeding rates between HeartMate II and HeartMate 3. Predictors for early bleeding events were lower pre- and postimplant platelet counts and ECMO support preimplantation. After multivariable adjustment, early bleeding events were associated with ECMO support preimplantation (odds ratio 6.3, 95% confidence interval 1.2–32.4; P  = 0.03) and thrombocytopenia (<150 × 10 9 /l) postimplant (odds ratio 5.9, 95% confidence interval 1.9–18.7; P  = 0.002). Patients who experienced an early bleeding event had a significantly worse 90-day survival rate compared to patients who did not (79% vs 96%, P  = 0.03). CONCLUSIONS: An early bleeding event needing surgical exploration is highly prevalent after LVAD implantation, especially in patients bridged with ECMO and with pre- and postimplant thrombocytopenia.